The multisensory design of pharmaceuticals and their packaging - Spence, C (Elsevier, 2021)
People’s expectations concerning the functional properties and efficacy of pharmaceuticals are influenced by a wide variety of product-extrinsic factors, such as the colour (of both product and pack), form (e.g., tablet vs. capsule), and shape (e.g., round, oval, or diamond-shaped) of medicines, and the multisensory design of the product packaging. The sound symbolic properties of a medicine’s brand name, as well as its processing fluency, have also been shown to exert a significant influence over people’s expectations. However, given that non-adherence has long been a key issues with medical treatment, further research is urgently needed in order to determine the extent (albeit likely limited) to which these various product-extrinsic factors influence non-compliance, while at the same time avoiding the confusion that has been caused by the proliferation of look-alike/sound-alike drugs in the marketplace in recent years. Further research is also needed in order to help establish the cross-cultural consensuality of the meanings that are attached by consumers to these various different product-extrinsic sensory cues (especially colour) in the pharmaceutical category, and to firmly establish the robustness of any colour-based placebo effects. At the same time, however, it is currently unclear which cue (or cues) dominate(s) when multiple product attributes are manipulated simultaneously given that the influence of colour, shape, sound symbolism, etc., have typically only been studied individually to date. The multisensory design of pharmaceuticals and their packaging therefore constitutes a particularly intriguing, not to mention important, applied area for food/sensory scientists, marketing researchers, and cognitive neuroscientists.